חלומות על מות ערבים: רומן אוסלו - פרנקו, לאון (מכאן, 2024)
This article identifies and conceptualizes an abstract literary genre: “the Oslo Novel”. Drawing on Fredric Jameson’s Political Unconscious it argues that formal literary genres - such as historical novels, romance novels, and detective fiction - also have an abstract political genre that manages their form and content in a different and more dominant fashion than the constraints of any formal genre. It raises the manner in which certain Israeli novels addressed the Israeli-Arab conflict in relation to Prime-Minister Ehud Barak’s statement, in July 2000, that the Palestinians were no “partners for peace”. This statement became a local commonplace and served as the official explanation for the political impasse, finding its way into narratives of acclaimed novels such as: La Maison Dajani (Alon Hilu, 2008), Borderlife (Dorit Rabinyan, 2015), and CrockAttack (Assaf Gavron, 2006).The controversial themes at the heart of these novels drew a positive critical reception, presenting them as political and subversive; this also led to their commercial success (Gavron’s book did not succeed domestically but did make a mark abroad). This present reading shows that, despite their subversive appearance, the novels produce elaborate justifications that enable the repression and stagnation of the Israeli-Arab conflict, and that this denial and deferral are governed by a capitalist mode of production.